The Epidemiology of Snakebite in Bhutan: A Retrospective Study - Tshokey, Tshokey; Jamtsho, Rixin; Rinchen, Sangay (Public health challenges, 2025)
Bhutan is a tropical country where snakebite is supposedly common, but official data are scanty and unmethodical. Deaths from snakebites were reported from areas where snakebites are common. Four‐year (2018–2021) data of snakebite from 45 Bhutanese hospitals were collected and analysed to describe the burden and map by districts. A total of 371 snakebites were recorded from 45 hospitals during the 4 years. Most cases were seen in the southern and central parts of the country. There was a definite rise in the number of cases in the warmer months, starting from March and peaking between June and August. About 240 (65%) of the bites occurred in males, and the highest number of snakebites occurred during farming ( n  = 100, 27%), bush walking ( n  = 42, 11.3%), herding ( n  = 15, 4%) and trekking ( n  = 1, 0.2%). The most common anatomical bite site was the leg ( n  = 167, 45.01%), followed by the hand ( n  = 81, 21.8%), finger ( n  = 56, 15.09%), toes ( n  = 11, 2.96%), thigh region ( n  = 6, 1.6%), head and face ( n  = 3, 0.8%), chest and shoulder ( n  = 3, 0.8%) and abdomen ( n  = 1, 0.3%). Most snakes were unidentified ( n  = 266, 71.7%). Those identified were vipers ( n  = 74, 19.9%), rat snakes ( n  = 12, 3.2%), kraits ( n  = 7, 1.88%), cobras ( n  = 6, 1.61%), river snakes ( n  = 5, 1.34%) and wolf snakes ( n  = 1, 0.26%). Forty‐three (11.6%) of the bite victims had resorted to non‐medical home treatment. Even with an obvious underreporting, snakebite is a significant public health problem, and Bhutan should embrace more public health and clinical activities to prevent morbidities and mortalities from snakebite.